PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KOMITMEN ORGANISASI DAN MOTIVASI TERHADAP KINERJA MANAJERIAL PADA KANTOR CAMAT KOTA LANGSA - sariati; Iqlima Azhar; Khairul Aswadi (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2020)
This studi aims to determine the effect of budgeting participation, organizational commitment, and motivation on managerial performance in the Langsa district office. The population in this study were all employees of the Langsa city sub-district office with 114 employees. The Sample in this study amounted to 88 respondents. The sampling technique used in this study is a stratified sampling technique that is by taking samples with attention to strata (levels). The data analysis method used in this study is the multiple linear regression equation Y2,534+0,161X1-0,048X2+0,326X3. The hypothesis test used in this study is a partial test (t test) and simultaneous test (F test). t test results show that budgetary participation variable significantly influences managerial performance, organizational commitment, does not affect managerial performance. F test results showed that budgetary participation, organizational commitment, and motivation variables significantly influenced managerial performance at the Langsa District office.